BRIDGING KNOWLEDGE AND ACADEMIC INTEGRITY: AI INTEGRATION FOR TPACK DEVELOPMENT IN EFL TEACHER EDUCATION PROGRAM - Kusuma, I Putu Indra; Budiarta, Luh Gd Rahayu; Maharani, Anak Agung Putri (LLT Journal: A Journal on Language and Language Teaching, 2025)
Recent research indicates that generative artificial intelligence (GenAI) such as ChatGPT has great potentials to support English as a foreign language (EFL) preservice teachers (PSTs) to develop their technological pedagogical content knowledge (TPACK) during their studies in teacher education programs (TEPs). How these PSTs view academic integrity while using GenAI and apply it for TPACK development are still unknown. Looking at the above gaps, this study aimed at exploring how EFL PSTs use GenAI to develop their TPACK and perceived academic integrity. This study recruited eight EFL PSTs in an Indonesian public education university using a basic qualitative methodology. This study employed semi-structured interviews and researchers’ notes to collect the data. The data in this work was analyzed using inductive thematic analysis. The results revealed that participants used AI for language skill development and for content creation as well as task assistance. The results also showed that they knew the potential risks of GenAI on academic integrity, had their own strategies for maintaining academic integrity when using GenAI, and had good impressions of academic integrity in AI-assisted learning. This study drew several theoretical and practical implications to support the application of GenAI in TEPs.